2008
DOI: 10.1063/1.3001926
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations of thermal resistance at the liquid-solid interface

Abstract: Heat conduction between parallel plates separated by a thin layer of liquid Argon is investigated using three-dimensional molecular dynamics (MD) simulations employing 6-12 Lennard-Jones potential interactions. Channel walls are maintained at specific temperatures using a recently developed interactive thermal wall model. Heat flux and temperature distribution in nanochannels are calculated for channel heights varying from 12.96 to 3.24 nm. Fourier law of heat conduction is verified for the smallest channel, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

19
134
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 160 publications
(153 citation statements)
references
References 18 publications
19
134
0
Order By: Relevance
“…Recently, the ITR has been computationally measured between two media. [26][27][28][29][30][31] These reports suggest that density is one of the key factors affecting the thermal resistance at the interface. For instance, an increase of the atomic density at the interface improves the probability of intermolecular interactions, resulting in an enhanced phonon transmission and, consequently, a reduced ITR.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the ITR has been computationally measured between two media. [26][27][28][29][30][31] These reports suggest that density is one of the key factors affecting the thermal resistance at the interface. For instance, an increase of the atomic density at the interface improves the probability of intermolecular interactions, resulting in an enhanced phonon transmission and, consequently, a reduced ITR.…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies supported the importance of Brownian motion for the enhanced thermal conductivity of nanofluids [35,36], there are other researchers against it [37,38]. As for the liquid layer at the liquid/particle interface, molecular dynamic simulations [39][40][41][42] discovered water density fluctuation near the solid surface representing the liquid layer and could explain the thermal behavior such as temperature jump on the surface, while some studies [43][44][45] indicated that the liquid layer might not influence the thermal behavior of nanofluids. In addition, Keblinski et al [44] found that ballistic heat transport still could not explain the anomalous thermal conductivity enhancements either.…”
Section: Introductionmentioning
confidence: 99%
“…As for the heat transfer, the small tension of a superhydrophobic surface may greatly decrease the interaction between a liquid droplet and the solid so that the superhydrophobic surface can supply anti-icing or anti-dewing properties, (1)(2)(3) control the solid-liquid thermal resistance, (4)(5)(6) and produce very high boiling heat transfer coefficient (7) .…”
Section: Introductionmentioning
confidence: 99%